The Role of Histone Lysine Methylation in the Response of Mammalian Cells to Ionizing Radiation - Di Nisio, Elena; Lupo, Giuseppe; Licursi, Valerio; Negri, Rodolfo (Frontiers in Genetics, 2021)
Eukaryotic genomes are wrapped around nucleosomes and organized into different levels of chromatin structure. Chromatin organization has a crucial role in regulating all cellular processes involving DNA-protein interactions, such as DNA transcription, replication, recombination and repair. Histones post-translational modifications (HPTMs) have a prominent role in chromatin regulation, acting as a sophisticated molecular code, which is interpreted by HPTM-specific effectors. Here, we review the role of histone lysine methylation changes in regulating the response to radiation-induced genotoxic damage in mammalian cells. We also discuss the role of histone methyltransferases (HMTs) and histone demethylases (HDMs) and the effects of the modulation of their expression and/or the pharmacological inhibition of their activity on the radio-sensitivity of different cell lines. Finally, we provide a bioinformatic analysis of published datasets showing how the mRNA levels of known HMTs and HDMs are modulated in different cell lines by exposure to different irradiation conditions.